Orthodontic treatment need from a bibliometric analysis of the last four decades: a bibliometric analysis - Yusra, Yohana; Kusnoto, Joko; Gunardi, Indrayadi; Goalbertus, Goalbertus; Kusnoto, Budi (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Malocclusion is a common oral disorder that strongly correlates with orthodontic treatment needs (OTN), however the complete picture of OTN remains unclear. This bibliometric study was conducted to develop a complete picture of the OTN from 1974-2022. The purpose of this study was to conduct a bibliometric analysis of scientific research pertaining to orthodontic treatment needs Methods: Type of study was bibliometric analysis. The term "orthodontic treatment need" was used to search for relevant articles in the Scopus database. VOSviewer, OpenRefine, and Tableau Public were used to illustrate the contributions of authors, journals, institutions, countries and the co-occurrence analysis and references analysis of the keywords. Result: There were 890 publications produced as a result of this study. Richmond emerged as the author with the most extensive publication record, having authored a remarkable 21 pieces that garnered a cumulative total of 524 citations.  The analysis reveals that the United Kingdom, Brazil, and the United States emerged as the primary contributors to literature pertaining to the assessment of orthodontic treatment necessity. The analysis of keywords revealed the occurrence of seven distinct clusters, which are: Index of Orthodontic Treatment (IOTN), orthodontic treatment, quality of life, orthodontic, malocclusion, and oral health-related quality of life. The largest cluster identified in the study was "malocclusion," encompassing factors such as prevalence, the Dental Aesthetic Index (DAI), treatment necessity, and the need for orthodontic intervention. Conclusion: In general, the number of articles addressing the need for orthodontic treatment has increased, particularly in the third and fourth decades. In the fourth decade, there were more articles about the IOTN that contained keywords directly related to the index, as well as self-esteem, quality of life, and its socio-demographic and socio-economic status correlation. KEYWORDSorthodontic treatment need; malocclusion; bibliometric; quality of life.